THE STRUCTURE OF AUSTRO-HUNGARIAN IMMIGRATION IN THE RUSSIAN EMPIRE - Andrei Ptitsyn (Гуманитарные и юридические исследования)
The article examines the process of resettlement of Austro-Hungarian citizens to Russia in the late XIX - early XX centuries. The author analyzes number, location, social and national composition of immigration.